2022
DOI: 10.18196/ftl.v7i1.13210
|View full text |Cite
|
Sign up to set email alerts
|

Developing E-Module of Islamic Reading Text Materials

Abstract: Providing English learning material with an Islamic basis for Madrasah Aliyah students is important as the students are Islamic learners. This research aims to develop an e-module of Islamic reading text materials for the second semester of tenth-grade students of MAN 1 Pontianak. The researchers adapted the Analyze, Design, and Develop phases of the ADDIE concept to develop this research product. The analysis phase was conducted by interviewing the English teacher to determine the suitable e-module to be desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
(16 reference statements)
0
7
0
Order By: Relevance
“…Reading materials are a collection of reading texts that contain the contents of teaching materials that are displayed with interesting visualizations which can be used as a practical way to introduce learning materials [20]. Reading materials in the e-module are equipped with pictures that attract the attention of readers, because they are presented beautifully according to the context of the learning materials in each subject taught to students in higher education.…”
Section: Resultsmentioning
confidence: 99%
“…Reading materials are a collection of reading texts that contain the contents of teaching materials that are displayed with interesting visualizations which can be used as a practical way to introduce learning materials [20]. Reading materials in the e-module are equipped with pictures that attract the attention of readers, because they are presented beautifully according to the context of the learning materials in each subject taught to students in higher education.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Rahman, Wibawa, and Sumantri's (2022) e-module has been published on the Google play store, but their study was an analysis of the learners and context for developing the product. Regarding the multimedia elements equipped in the e-module in those studies, the e-modules were equipped with videos made by the researchers (Agustina & Efendi, 2021), and videos from YouTube (Berlin et al, 2022). The current study is different from those discussed previously.…”
Section: Introductionmentioning
confidence: 94%
“…The findings showed that, based on students' evaluation of the e-module in trials 1 and 2, the e-module had the feasibility to be used in online and offline systems. Similarly, Berlin, Apriliaswati and Rezeki's (2022) study on developing emodule also integrated Islamic values in recount and narrative English reading texts. The e-module involved multimedia elements such as videos from YouTube, pictures and links for the exercises.…”
Section: Introductionmentioning
confidence: 99%
“…Copyright© 2023 Siswoyo, Fatma Yuniarti content based on teaching vocabulary (Putra, 2017), reading (Berlin et al, 2022), and orientation of Islamic reading materials (Nur & Noorbani, 2019). This article is to complete the existing research on the perception of the materials from the teachers' point of view.…”
Section: Elt-lectura: Studies and Perspectives In English Language Te...mentioning
confidence: 99%